A comparison between vinyl nitrile foam and new air chamber technology on attenuating impact energy for ice hockey helmets - Gimbel, G.; Hoshizaki, T. B. (International Journal of Sports Science and Engineering, 2008)
Head injuries incurred while playing ice hockey result from a range of impact energies. The objective of this study was to compare the impact energy attenuation range of conventional multi-impact materials incorporated in ice hockey helmets to a new multi-impact technology, referred to as a `chamber`. Three densities of 2.6 cm thick vinyl nitrile foam and two hardness values of the chamber were impacted at three drop heights and three drop masses using a free drop rig. The drop masses were chosen to represent the head mass of a young child up to an adult in order to show the level of protection provided for different head masses. Three PCB 203B force sensors collected force data at 20 kHz directly above the y axis of the impact and acceleration was calculated from the force values. Analysis revealed significant differences in peak linear acceleration between the vinyl nitrile and the dynamic air chambers (p<0.001). The chambers performed better throughout more impact conditions than the foam.